The marine fauna of New Zealand : Index to the fauna 1 Protozoa - Dawson, Elliot W. (Wellington, New Zealand NZ Oceanographic Institute, 1992)
Nnew Zealand Oceanographic Institute Memoir; 99
Keywords: Marine fauna-New Zealand; Marine fauna; copepoda